Voyage around my screen, voyage around with my screen: space perception from physical, through digital, to hybrid. (2017) - Papakonstantinou, Giorgos ?.
Navigating and communicating within urban space is fundamental in everyday life activity. Human spatial conception and experience could be categorised in three different states: 1) presence in the physical environment; 2) presence in a virtual environment, mediated by representation technologies, either analogue or digital; 3) mental presence in an imaginary environment. This text focuses on the emergence of a fourth state of spatial experience, that of the synthetic spatial context, afforded by mobile computing and location detection technologies. Contemporary urban environments offer a multiplicity of layers of information (social, historical, etc.) through material elements and display systems communication. Mediated spatial activity in digital environment is mapped onto the physical, urban environment. Thus, mediated digital content and physical spatial experience are projected onto the urban space.